Successful Management of a Cystic Lesion Which Had Been Caused by Menstrual Blood Above the Dehiscence of Cesarean Incision Scar: Case Report - Uğur Keskin; Fahri Burçin Fıratlıgil; Mustafa Ulubay; Ulaş Fidan; Rıza Efendi Karaca; Ali Ergün (Medical Network, 2016)
Cesarean scar dehicence has the incidence of 1.2% after base transverse incisions. Beside causing a situation increasing morbidity and mortility for baby and mother and needing acute intervention in antenatal or intrapartum period by causing uterine rupture, it is an important complication that can cause sudden bleeding, infection and even uterine fistules in postpartum period. In our case, we will mention about the successful management of cyst caused by menstrual blood that develops dehiscence of cesarean scar. A female patient with the age of 40 (Gravida:2, parity:2 (2 C/S) applied to our policlinic because of amenorrhoea. A cystic mass, probably originated from cesarean incision scar, with intense content, smooth borders and the dimensions of 66x24 mm was observed by the help of transvaginal ultrasonography. The evacuation of the cyst content had been decided by performing vacuum aspiration from cervical ostium. Transabdominal ultrasonography guided karman cannula was placed into the cyst from cervical ostium. The content of the cyst had been aspired by negative pressure. Most of the complications after cesarean can be diagnosed by easy ultrasonographic observations and physical examinations, some needs expensive radiologic observations such as magnetic resonance imaging, computerized tomography, while for some of them, second- look procedures can be necessary that increase mortality and morbidity of the patient. The most important thing is how to treat these complications. Some of them can be treated by conservative approaches; while some of them needs severe surgical operations even histerectomy. As in our case, the cyst caused by menstrual blood after causing dehiscence of cesarean scar, was vacuum aspirated easily and treated by conservative approach.